Demographic collapse, Indian Peru, 1520-1620 - Cook, Noble David (Cambridge Latin American studies, 1981)
While many scholars have been interested in the size of the Indian population of the Americas at the time of first contact with Europeans, this book, first published in 1982, was the first to make a thorough examination of the question. Focusing on Peru, Professor Cook estimates population size on the basis of archaeology, carrying capacity of the agricultural systems, disease mortality, depopulation ratios, and census projection. He also analyses the catastrophic population decline that resulted from contact with Europeans, and compares this experience with that of the coastal region and the Andean highlands